Analisis Kebutuhan Pengembangan Media Audiovisual Materi Pembelajaran Iklim Dan Perubahannya Terhadap Kehidupan Sosial di Sekolah Dasar - Siti Rohmatul Janah; Hartono Hartono; Farhan Yadi (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2006)
This study aims to analyze the need for developing audiovisual learning media using Canva in science learning on climate change for fourth-grade elementary school students. The study used a quantitative descriptive approach with a needs analysis questionnaire as the data collection technique. The research subjects consisted of 35 fourth-grade students and 2 fourth-grade teachers at Muara Medak Elementary School. The research instrument was a questionnaire containing 10 statements with a rating scale from very high to very low. Data were analyzed using a percentage technique based on pedagogical, technical, cognitive, and aesthetic aspects. The results showed that the need for audiovisual media development was in the high to very high category, with a percentage of 84.57% for the pedagogical aspect, 81.85% for the technical aspect, 76.28% for the cognitive aspect, and 85.42% for the aesthetic aspect. These findings indicate that students and teachers need learning media that are interesting, easily accessible, and able to help understand abstract material. Based on these results, the development of audiovisual media using Canva is considered relevant as a learning solution to increase learning interest and support the effectiveness of science learning in elementary schools.